2014
DOI: 10.1186/2045-3701-4-39
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 null enhances UVB-induced skin inflammation and extracellular matrix damages

Abstract: Nrf2 plays a critical role in defending against oxidative stress and inflammation. We previously reported that Nrf2 confers protection against ultraviolet-B (UVB)-induced inflammation, sunburn reaction, and is involved in sulforaphane-mediated photo-protective effects in the skin. In this study, we aimed to demonstrate the protective role of Nrf2 against inflammation-mediated extracellular matrix (ECM) damage induced by UVB irradiation. Ear biopsy weights were significantly increased in both Nrf2 wild-type (Nr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 32 publications
(45 reference statements)
1
56
0
Order By: Relevance
“…Nevertheless conclusive results would benefit of using knockout mice, which are experiments now underway in our lab. In this sense our results also are in agreement with a previous report by Saw et al [58] showing that Nrf2 null (C57BL/6 mice) enhances UVB (a single dose of 300 mJ/cm 2 )-induced skin inflammation and extracellular matrix damages. Moreover, recent findings also indicate that the tumor suppressor activity of p53 is related to its role in maintaining cellular redox by regulating cellular metabolism [51].…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless conclusive results would benefit of using knockout mice, which are experiments now underway in our lab. In this sense our results also are in agreement with a previous report by Saw et al [58] showing that Nrf2 null (C57BL/6 mice) enhances UVB (a single dose of 300 mJ/cm 2 )-induced skin inflammation and extracellular matrix damages. Moreover, recent findings also indicate that the tumor suppressor activity of p53 is related to its role in maintaining cellular redox by regulating cellular metabolism [51].…”
Section: Discussionsupporting
confidence: 94%
“…These results are in line with several studies that reported the pivotal role of Nrf2 in the endogenous cellular protection response against the damaging effect of UVB. For example, Saw et al [46] have found that Nrf2-knockout mice were more susceptible to UVB-induced damage and mutagenesis. In addition, Nrf2 was suggested to be a key regulator in the complex interplay between keratinocytes and melanocytes under UVB radiation by a paracrine MAPK-dependent pathway [47].…”
Section: Resultsmentioning
confidence: 99%
“…Exhibiting a wide spectrum of cytoprotective effects in a variety of skin models including inflammatory and UV-induced oxidative damage, HO-1 induction was suggested as a marker diagnosis of oxidative stress related conditions [68,69].…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…Compelling evidence indicates that these enzymes are of high importance maintaining skin redox balance homeostasis and protecting the epidermis against oxidative damage-related conditions and diseases, including skin erythema, inflammation, wound healing and skin cancers [14,69,74,75]. It was reported that patients suffering from actinic keratoses and basal cell carcinoma (BCCs), common non-melanoma skin cancer, had reduced levels of antioxidant enzymes in plasma or serum [76].…”
Section: Antioxidant Enzymesmentioning
confidence: 99%